An effective and efficient protocol for propagating large files in Peer-to-Peer systems - Hoque, Md Jiabul (IIUC Studies, 2023)
Distributed Hash Tables (DHTs) are integral components in peer-to-peer systems, providing storage and lookup services for key-value pairs. While they have proven highly successful in managing and locating replicas of small files (typically under 1 MB), their efficiency in handling larger files diminishes. Factors like sluggish data senders and slow receivers further exacerbate the inefficiencies in peer-to-peer systems, causing delays in the file propagation process. To address these challenges, peer-to-peer systems require more efficient protocols and resources to expedite the handling of relatively large data files. This study introduces a novel, efficient, and effective mechanism to propagate substantial files within DHTs while balancing load and minimizing system overhead. To assess the proposed protocol's effectiveness, we evaluated using the PeerSim simulator. We analyzed two crucial metrics linked to our proposed system: overhead and propagation time. The outcomes of this research demonstrate a significant reduction in propagation time while system overhead remains minimal. Consequently, the proposed protocol can ensure seamless operation in real-world streaming applications. IIUC Studies, Vol.-20, Issue-1, June 2023, pp. 141-166